2014
DOI: 10.1111/iju.12544
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patient and technical factors associated with midurethral sling mesh exposure and perforation

Abstract: Objectives To evaluate the technical and patient characteristics associated with the development of mesh perforation and exposure in patients after midurethral sling surgeries. Methods After a retrospective review of referred patients, the risk of mesh perforation of the urinary tract over exposure in the vagina was analyzed with multivariate logistic regression, adjusting for the possible predictors of age, body mass index, smoking status at the time of mesh placement, presence of diabetes, type of sling pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
0
25
1
Order By: Relevance
“…The true incidence of mesh perforations is unknown, but it is estimated to be 0.7-5 % for retropubic slings and 0-0.5 % for transobturator slings [31,59]. It is unclear whether a mesh perforation results from progressive erosion of the mesh over time or from a missed perforation at the time of the procedure [22].…”
Section: Mesh Perforation and Urinary Fistulamentioning
confidence: 99%
See 1 more Smart Citation
“…The true incidence of mesh perforations is unknown, but it is estimated to be 0.7-5 % for retropubic slings and 0-0.5 % for transobturator slings [31,59]. It is unclear whether a mesh perforation results from progressive erosion of the mesh over time or from a missed perforation at the time of the procedure [22].…”
Section: Mesh Perforation and Urinary Fistulamentioning
confidence: 99%
“…In a retrospective review by Osborn et al, 27 patients were identified to have a post-operative MUS perforation (bladder perforation n = 12, urethral perforation n = 15). Of these, 11/27 (41 %) presented with irritative voiding symptoms, 7/11 (26 %) incontinence, 4/11 (15 %) vaginal pain, and 2/11 (7 %) with either recurrent UTIs or dyspareunia [59].…”
Section: Mesh Perforation and Urinary Fistulamentioning
confidence: 99%
“…148,[239][240][241][242] However, in an article published in 2014, the authors concluded that occurrence of bladder and/or urethral perforations during surgery is associated with an almost 26-fold increase in risk of subsequent bladder or urethral mesh erosion. 31 If the findings of this study are accurate, the dictum of simply removing and repassing the trocar after bladder p erforation must be seriously questioned. Limited information is available on urethral complications following perforation, but if a perforation large enough to necessitate repair exists, most would agree that it is best to abandon the SMUS procedure.…”
Section: Reviews Infectionmentioning
confidence: 92%
“…Currently, the gold standard for surgical management of SUI in women is the midurethral sling (MUS), which displays a cure rate of 80-95% [6][7][8]. While MUS has a high success rate, 5-20% of the patients will have persisting incontinence thus needing to undergo sling removal and subsequent treatment [9]. The postoperative complications reach as high as 7.2% for erosion and the risk of getting a perioperative urinary tract infection is 17.2% [10].…”
Section: Aimmentioning
confidence: 99%